Shear Strength and Pull-Out Response of Tire Shred-Sand Mixture Reinforced with Deformed Steel Bars - Beenish Jehan Khan; Irshad Ahmad; Hassan Nasir; Abdullah Abdullah; Qazi Khawar Gohar (Advances in Civil Engineering)
The use of scrap tires in various engineering applications has been extensively explored. The present study has the following aim: to evaluate the suitability of tire-sand mixtures as backfill material based on its shear strength. To achieve this objective, modified Proctor compaction tests were performed on tire shred-sand mixture with mixing proportions by weight of tire shreds and sand (0/100, 20/80, 30/70, and 40/60) using different sizes of tire shreds (50 mm, 75 mm, and 100 mm). Based on the results of the modified Proctor compaction test, the two mixing proportions, i.e., tire shred/sand, 20/80 and 30/70, respectively, were selected. Large-scale direct shear test indicated higher internal friction angle and cohesion values for tire shred-sand mixtures (30/70) with 100 mm tire size (38.5° and 19 kPa) as compared with sand-only backfill material (30.9° and 0 kPa). Based on stress-strain behavior plots, it was indicated that the inclusion of tire shreds imparts ductility to backfill mixtures. To achieve the second objective, the pull-out tests were performed with deformed steel bars of two different diameters (12.7 mm and 15.8 mm) embedded in various backfill mixtures prepared with tire shreds of three different sizes (50, 75, and 100 mm). The pull-out test result indicated that the deformed steel bars exhibit higher pull-out resistance in tire shred-sand mixtures (9.9 kN/m) compared with sand-only backfill material (4.1 kN/m).